Penciptaan Motif Batik dari Legenda Pulau Kemaro pada Busana Pengantin Wanita - Handayani, Mery; Sukanadi, I Made; Aruman, Aruman (Style : Journal of Fashion Design, 2023)
The creation of this Final Project is entitled Creation of Batik Motifs from the Legend of Kemaro Island on the Bride's Dress. The legend of Kemaro Island is an archipelago legend originating from Palembang. This legend tells of the love story of a Chinese merchant and Princess Sriwijaya who are the origins of Kemaro Island. The legend of Kemaro Island is visualized in the bride's attire. This work of clothing can be enjoyed as a whole, both in use and beauty. The making of this work aims to introduce the Legend of Kemaro Island to the public through the art of batik which is designed with wedding attire. In the creation of this final project, the author made 6 (six) designs for the bride's dress, but only 2 designs were made into ready-to-wear works, each of which has its own characteristics, the uniqueness of which makes the wedding dress created have high quality and aesthetic value. interesting